GNP enhanced responses in microdosimetric spectra for 192Ir source - Hsing, Chun-Hui; Cho, I-Chun; Chao, Tsi-Chian; Hong, Ji-Hong; Tung, Chuan-Jong (Radiation measurements, 2018)
The potential radiosensitizing effects of gold nanoparticles (GNPs) in radiation therapy have been extensively studied. GNPs loaded in the tumor produce a large number of low-energy secondary electrons which contribute to the local dose enhancement and elevate the relative biological effectiveness (RBE). Thus GNP enhanced responses in 192Ir, a widely used brachytherapy source, are the subject of interest. These radiosensitizing effects can be examined through comparisons between microdosimetric spectra of secondary electrons resulting from the 192Ir in the presence and absence of GNPs in cells. Measurements of single-event lineal energy spectra give indications of a relative therapeutic advantage. In the present work, a mini tissue equivalent proportional counter (TEPC) was constructed to measure the microdosimetric spectra in cells containing and without GNPs for 192Ir source. A plug, either contained a 50 nm-thick gold foil coated on its inner surface or without the foil, was inserted into the TEPC wall during measurements. Analyses of the measured un-normalized and normalized dose lineal energy spectra provided information on the enhancements in absorbed dose and RBE. The dose enhancement was 1.27 and 1.37 for 1 and 0.5 μm-diameter sites, respectively. The increase in dose enhancement with decreasing site diameter revealed the sharp fall-off in the local dose enhancement. Applying the biological weighting function method, the RBE enhancement was 1.32 based on the lineal energy spectra of 1 μm site. •A mini TEPC was constructed with two A150 plastic plugs, one coated with a 50 nm-thick gold foil on its inner surface.•The mini TEPC was used to determine the dose and RBE enhancements near the gold-tissue interface under 192Ir irradiation.•Analyses of the dose lineal energy spectra yielded the dose enhancement of 1.27 and 1.37 for 1 and 0.5 μm-diameter sites.•Analyses of the dose-mean lineal energies yielded 1.29 and 1.33 for 1 and 0.5 μm-diameter sites.•Based on the biological weighting function method, the RBE enhancement was 1.32 for a 1 μm-diameter site.